Knowledge from data in the built environment - Starkey, Christopher; Garvin, Chris (Annals of the New York Academy of Sciences, 2013)
Data feedback is changing our relationship to the built environment. Both traditional and new sources of data are developing rapidly, compelled by efforts to optimize the performance of human habitats. However, there are many obstacles to the successful implementation of information‐centered environments that continue to hinder widespread adoption. This paper identifies these obstacles and challenges and describes emerging data‐rich analytic techniques in infrastructure, buildings, and building portfolios. Further, it speculates on the impact that a robust data sphere may have on the built environment and posits that linkages to other data sets may enable paradigm shifts in sustainability and resiliency.